1974
DOI: 10.1126/science.186.4169.1130
|View full text |Cite
|
Sign up to set email alerts
|

Target Structure and Echo Spectral Discrimination by Echolocating Bats

Abstract: Echolocating bats can use sonar to discriminate among targets which reflect echoes differing in spectral distribution of energy but not in overall intensity. They can detect differences smaller than 1 millimeter in fine target structure. Bats may be capable of classifying targets from echo spectral signatures and might thus be able to distinguish among flying insect prey by sonar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 9 publications
(11 reference statements)
6
77
0
Order By: Relevance
“…Carollia produces broadband and high-frequency FM signals which are well suited for this task. Hence, Carollia could potentially use dierences in surface texture as a cue to distinguish ripe from unripe fruits and fruits from other objects by analyzing dierences in the spectral or temporal signature of the returning echo (Bradbury 1970;Habersetzer and Vogler 1983;Mogdans and Schnitzler 1990;Ostwald et al 1988;Schmidt 1988;Simmons and Vernon 1971;Simmons et al 1974Simmons et al , 1995. However, our study with untrained bats in the¯ight cage showed that both species approached, and even bit into foam rubber models of Piper which clearly diered in surface structure from real fruits.…”
Section: Role Of Surface Structurementioning
confidence: 41%
“…Carollia produces broadband and high-frequency FM signals which are well suited for this task. Hence, Carollia could potentially use dierences in surface texture as a cue to distinguish ripe from unripe fruits and fruits from other objects by analyzing dierences in the spectral or temporal signature of the returning echo (Bradbury 1970;Habersetzer and Vogler 1983;Mogdans and Schnitzler 1990;Ostwald et al 1988;Schmidt 1988;Simmons and Vernon 1971;Simmons et al 1974Simmons et al , 1995. However, our study with untrained bats in the¯ight cage showed that both species approached, and even bit into foam rubber models of Piper which clearly diered in surface structure from real fruits.…”
Section: Role Of Surface Structurementioning
confidence: 41%
“…The limited temporal resolution led to the conclusion that bats generally evaluate echoes in the frequency domain when time differences of less than 100·s in overlapping echoes are offered (Beuter, 1980;Simmons et al, 1974). Nevertheless, behavioural experiments showed that Eptesicus fuscus perceives electronically generated echoes of two front targets in terms of two distinct reflections, and this with a resolution of up to 2·s (Simmons, 1989;Simmons et al, 1998).…”
Section: Temporal Pattern and Spectral Domainmentioning
confidence: 99%
“…Ostwald et al, 1988;Schmidt, 1988;Schmidt, 1992;Schnitzler and Henson, 1980;Simmons et al, 1974). Hitherto the objects used for object recognition tasks were such that their echo heavily changed with the angle of sound incidence (Bradbury, 1970;Simmons et al, 1974;Simmons and Vernon, 1971), which renders it difficult to determine the decisive echo feature. We used the simplest possible concave form, the hollow hemisphere, because of its extraordinary acoustic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior ofbats in nature and in laboratory experiments shows that the shape oftargets is encoded in sonar sounds (see, e.g., Busnel & Fish, 1980;Griffin, Friend, & Webster, 1965;Simmons et al, 1974). However, sonar sounds have many different dimensions (amplitude changes, frequency composition, cross-correlation between the emitted sound and the returning echo, and so on).…”
Section: Examining the Availability Of Information And Its Representamentioning
confidence: 99%